2021
DOI: 10.1101/2021.03.21.436363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of high dimensional flow cytometry and unsupervised analysis to define the immune cell landscape of early childhood respiratory and blood compartments

Abstract: The cellular landscape of the paediatric respiratory system remains largely uncharacterised and as a result, the mechanisms of highly prevalent childhood respiratory diseases remain poorly understood. A major limitation in defining mechanisms of disease has been the availability of tissue samples collected in early life, as well as technologies that permit deep immune analysis from limited sample volumes. In this work, we developed new experimental methods and applied unsupervised analytical tools to profile t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…This indicates that, in healthy children, systemic cytokine levels may not reflect those in the lung, although we acknowledge the smaller number of participants with matched samples for this analysis. These findings are similar to our previous work that showed no significant correlation in immune cell type proportions between healthy paediatric blood and airway samples (15). While our data suggest that circulating immune markers may not be good proxies for the lung immune response in healthy children, studies investigating respiratory conditions such as asthma, severe COVID-positively correlate with those in BAL during disease (29)(30)(31).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This indicates that, in healthy children, systemic cytokine levels may not reflect those in the lung, although we acknowledge the smaller number of participants with matched samples for this analysis. These findings are similar to our previous work that showed no significant correlation in immune cell type proportions between healthy paediatric blood and airway samples (15). While our data suggest that circulating immune markers may not be good proxies for the lung immune response in healthy children, studies investigating respiratory conditions such as asthma, severe COVID-positively correlate with those in BAL during disease (29)(30)(31).…”
Section: Discussionsupporting
confidence: 90%
“…Non-canonical NFκB signaling regulates cell survival, maturation, and proliferation, as well as plays a key role in the development of immune tissues, highlighting the importance of these pathways in early life (14). We also recently showed that proportions of immune cell types associated with JAK/STAT and NFκB signaling, including conventional dendritic cells, monocytes, and B cells, also reduced with age in blood of children (15) , providing a potential further link between these pathways and immune development in childhood.…”
Section: Discussionmentioning
confidence: 83%